Recensione a: Novalis, La Cristianità o Europa - Flavio Tisi (Rosenberg & Sellier, 2015)
This is a review of “Christianity or Europe”, an essay written by Novalis in 1799. It focuses on the author’s thesis (namely, the identification of Christianity and Europe), by presenting and analysing the arguments he provides in defence of his view. Finally, there is a critical assessment of the value Novalis’ work has nowadays.